Stochastic simulation and analysis of the operation of computing systems with structural redundancy - Pavskii, V. A.; Pavskii, K. V. (Optoelectronics, instrumentation, and data processing, 2014)
One way to increase the reliable and robust operation of large-scale computing systems is to introduce a reserve (a structural redundancy system) to them. A model for the analysis of the operation of distributed computing systems is proposed. The results of analytical and simulation modeling are presented. Flows of events with a Weibull distribution (shape parameter values of 1 and 0.78) are considered..